Does academic motivation contribute to the self-esteem of students at the graduate level? A case study of universities in the southern districts of Khyber Pakhtunkhwa, Pakistan - Ullah, Hikmat; Shahzada, Gulap; Khan, Habib Nawaz (Frontiers in Education, 2024)
This study explored the impact of students' academic motivation of students on self-esteem at the graduate level. The respondents of this study were 375 university students, enrolled in BS programme of 09 disciplines from all the four public sector universities of Southern districts of Khyber Pakhtunkhwa. Krejcie & Morgan (1970) formula was used for sample size. Two standardized questionnaires i.e. Academic Motivation Scale, a tool consisting of 28 items for measuring academic motivation and Rosenberg's scale for measuring self-esteem, consisting of 10 items that measure self-respect by assessing both the aspects, positive and negative emotional states about the self, were used. In light of the objectives and hypotheses, Mean, SD were used to find out the level of academic motivation and self-esteem of the students. Linear egression was applied to find out the impact of students' academic motivation on their self-esteem. Moreover, an independent t-test was used to explore the difference in academic motivation and self-esteem between male and female students. There was no significant difference in the academic motivation and self-esteem of the students at the graduate level. The results showed that the university students at the graduate level had a high level of academic motivation and self-esteem.A unit change in overall academic motivation, knowledge and stimulation parts of intrinsic motivation and identified and external regulation of extrinsic motivation bring 0.678, 0.218, 0.223, 0.122 and 0.172 change in self-esteem respectively while the constructs i.e. accomplishment (Intrinsic motivation), introjected (extrinsic motivation) and amotivation are non-significant as p > .05.